The rationale and conditions for the issuing of Polish treasury bonds on foreign markets - Sylwia Frydrych (e-Finanse: Financial Internet Quarterly, 2019)
The aim of this article is to present the analysis of treasury bonds issued by the Ministry of Finance on international financial markets to finance debt. The author identifies the structure of bonds on the domestic and international markets. The study attempts to answer the question of whether the Ministry of Finance should issue bonds on foreign markets and what kinds of risk should be understood in the process of managing issues.
Keywords: H63; G10; G15; 330; foreign debt; bonds; debt issue